Proses Pengambilan Keputusan dalam Adopsi Inovasi Stimulan Organik Melalui Analisis Peran Pemangku Kepentingan - Wa Ode Muliastuty Arsyad; Esti Rini Satiti; Sukadaryati Sukadaryati (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2019)
Wood vinegar-based stimulant is potential to be developed in Perhutani, therefore, the process of adoption is indispersable to be analyzed. This study aims at identifying the involved stakeholders and analysing the relationships among stakeholders in the policy of adopting stimulant innovation in Perhutani areas. Respondents are selected using a snowball sampling method. Stakeholder analysis is performed by using Interpretative Structural Modeling (ISM) while stakeholder relations analysis is carried out by classifying the relation into five categories: interaction, continuity, synergy, strength, and the presence or absence of conflicts. The results shows that the stakeholders involved in the stimulants innovation adoption policy are mostly in Quadrant IV or performs that Perhutani officials have legal authority in decision-making process. The pine tappers in Quadrant I implies that they have limited influence to stimulants innovation adoption policy but they have enormous interest in the management of pine forests. Academicians, researchers, forest rangers, forestry services officials and Ministry of Environment and Forestry officials are in Quadrant II. They play important role as intermediaries or facilitators and have considerable influence on decision-making process. Interaction, synergy and relationship continuity among stakeholders are well-established, except among researchers and academicians. Meanwhile, they could colaborate research with Perhutani.